Estudos de compostos de coordenação formados a partir de ligantes diimínicos e suas propriedades luminescentes e biológicas - Chagas, Camila dos Santos [UNIFESP] (2017)
In this project, we discuss the synthesis and characterization of new coordination compounds based on the 5-nitro-8-hydroxyquinoline, 5-chloro-8-hydroxyquinoline and bipyridine ligands and their biological and luminescent properties. Synthesis of the complexes [Zn(5-nitro-8-oxyninoline2'-bipyridine]CF3SO3, [Al(5-nitro-8-oxyminoline)2]CF3SO3, [Cu(5-nitro-8-oxyminoline)2], [RuCl(NO)(5-chloro-8-oxyquinoline)2], [RuCl(NO)(5-nitro-8-oxyquinoline)2], [Zn(5-chloro-8-oxyminoline)2'2-bipyridine]CF3SO3, [Al(5-chloro-8-oxyminoline)2]CF3SO3, [Cu(5-chloro-8-oxyminoline)2] and [RuCl(NO)(5-chloro-8-oxyquinoline)2] were performed and their characterizations utilized spectroscopic techniques, including Infrared Vibrational Spectroscopy, which allowed changes in the frequencies of characteristic nC=N e o nC=C bands, proving the formation of the complexes. UV-vis spectroscopy allowed the identification of the specific bands of ligands, such as the π→π * transitions of the quinolinic ring and MLCT bands for some complexes. 1H-NMR showed the signal displacements after the complexation, which affect most strongly the complexes studied affect at the 2-H, 4-H and 6-H position of the 5-nitro-8-hydroxyquinoline and 5-chloro-8-hydroxyquinoline ligands. After the chemical characterization of the compounds, biological assays were performed in the laboratory at the Faculdade de Medicina do ABC, evaluating the cytotoxicity of the compounds, such as hematological analysis and coagulation analysis, which in general did not present high toxicity. This characteristic was also observed in the evaluation of the enzymes of the hepatic and renal profiles. For the analysis of the antimicrobial action strains of Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis Staphylococcus aureus and Candida albicans were used, defining the minimum inhibitory concentration. This analysis showed a better antimicrobial action for the complex [RuCl(NO)(5 chloro-8-oxyquinoline)2] compared to the other complexes. The complexes [Zn(5-nitro-8oxiquinolina)2’2-bipiridina]CF3SO3, [Cu(5-nitro-8oxiquinolina)2] e [RuCl(NO)(5-nitro-8oxiquinolina)2] showed promising antineoplastic action for the MCF-7 cell, indicating that this class of compounds may present good candidates for future development, and offer alternatives for new therapies.